Risk Analysis of Occupational Disease and Accident in Environmental Health Laboratory - Naomi Cimera1, Dani Nasirul Haqi1, Putri Ayuni Alayyannur1, Y.Denny Ardyanto1, Nur Laili Rizkiawati1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Risk analysis is a process to identify hazards by calculating the size of the risks and determining whether a risk is acceptable or not. The purpose of this study is to do hazard identification and risk assessment in environmental health laboratories at Faculty of Public Health at Universitas Airlangga. This study was included in an observational and cross sectional study based on the time of his research. Primary data is obtained through laboratory observations and interviews with reports presented in the form of tables and diagrams then analyzed descriptively. The results of this study indicate that in environmental health laboratories Faculty of Public Health Universitas Airlangga there are 10 potential hazards with 12 risks out of 4 activities. Based on the results of the risk assessment, from 12 risks there are 5 types of risks with low risk category, 4 types of risk for with moderate risk category, and 3 types of risk with high risk category. The conclusion of this study is that the greatest risk level in environmental health laboratories is low risk category of 41.67%. While for the moderate risk category was 33.33% and the high risk category was 25%. Risks with high risk categories include power failure, fire, and explosion at a time caused by the flow of electric current and chemical reactions carried out in the laboratory.